A signal - Bishop, J. (IEEE Transactions on medical imaging)
In quasi-static magnetic resonance elastography, strain images of a tissue or material undergoing deformation are produced. In this paper, the signal/noise (S/N) ratio [SNR] of elastographic strain images, as measured by a phase-contrast technique, is analyzed. Experiments are conducted to illustrate how diffusion-mediated signal attenuation limits maximum strain SNR in small displacement cases, while the imaging point-spread function limits large displacement cases. A simple theoretical treatment agrees well with experiments and shows how an optimal displacement encoding moment can be predicted for a given experimental set of parameters to achieve a maximum strain SNR. A further experiment demonstrates how the limitation on strain SNR posed by the imaging point-spread function may potentially be overcome.